The immediately releasable pool of secretory vesicles in adrenal chromaffin cells - Marengo, Fernando Diego (2013)
In neuroendocrine cells, such as adrenal chromaffin cells, the exocytosis of hormone-filled vesicles is triggered by a localized Ca2+ increase that develops after the activation of voltage-dependent Ca2+ channels. To reach the fusion competent state, vesicles have to go through a series of maturation steps that involve the detachment from cytoskeletal proteins, docking and priming. However, the fusion readiness of vesicles will also depend on their proximity to the calcium source. The immediately releasable pool is a small group of ready?to-fuse vesicles, whose fusion is tightly coupled to Ca2+ entry through channels. Recent work indicates that such coupling is not produced by a random distribution between vesicles and channels, but would be the result of a specific interaction of immediately releasable vesicles with particular Ca2+ channel subtypes. The immediately releasable pool is able to sustain, with high efficiency, the secretion triggered by the small and localized Ca2+ gradients produced by brief depolarizations at low frequencies, like action potentials at basal conditions in adrenal chromaffin cells.